Inner Ear Genes Underwent Positive Selection and Adaptation in the Mammalian Lineage - Pisciottano, Francisco (2019)
The mammalian inner ear possesses functional and morphological innovations that contribute to its unique hearing capacities. The genetic bases underlying the evolution of this mammalian landmark are poorly understood. We propose that the emergence of morphological and functional innovations in the mammalian inner ear could have been driven by adaptive molecular evolution. In this work, we performed a meta-analysis of available inner ear gene expression data sets in order to identify genes that show signatures of adaptive evolution in the mammalian lineage. We analyzed ∼1,300 inner ear expressed genes and found that 13% show signatures of positive selection in the mammalian lineage. Several of these genes are known to play an important function in the inner ear. In addition, we identified that a significant proportion of genes showing signatures of adaptive evolution in mammals have not been previously reported to participate in inner ear development and/or physiology. We focused our analysis in two of these genes: STRIP2 and ABLIM2 by generating null mutant mice and analyzed their auditory function. We found that mice lacking Strip2 displayed a decrease in neural response amplitudes. In addition, we observed a reduction in the number of afferent synapses, suggesting a potential cochlear neuropathy. Thus, this study shows the usefulness of pursuing a high-throughput evolutionary approach followed by functional studies to track down genes that are important for inner ear function. Moreover, this approach sheds light on the genetic bases underlying the evolution of the mammalian inner ear.